Heutagogy in Arabic Class: How It Is Applied in The Islamic Education Study Program of Universitas Islam Riau - Saproni Muhammad Samin (Jurnal Alsinatuna, 2019)
This study aims to identify the Arabic language curriculum in the Study Program of Islamic Education at the Universitas Islam Riau and Arabic language learning through the heutagogy approach. This research is qualitative research using descriptive analysis method. The study was conducted at the study program of Islamic Education. The study program of Islamic Education as well as social situation. Data collection in this research was carried out in three ways: Interview, Documentation, and Library research. In analyzing data, the writer uses descriptive analysis. The conclusion of this study is that the Heutagogy approach cannot be fully applied in teaching Arabic in the study program of Islamic Education, because the goal of learning Arabic cannot come out of the goals set by the Study Program. However, the spirit of heutagogy can be applied in the process of learning Arabic in the study program of Islamic Education with several Heutagogy approaches.